RECENT OBSERVATIONS OF Elephas maximus sumatranus IN SEMBILANG NATIONAL PARK, SOUTH SUMATRA - Hidayat, Benny; Travolindra, Yoga; Ridwan, Alex; Erwin, Suendi; Yustian, Indra (Biology Department, Faculty of Mathematics and Natural Sciences, Sriwijaya University, 2019)
Sumatran elephants (Elephas maximus sumatranus) are one of four Asian elephants subspecies, which are categorized as Critically Endangered by the IUCN (International Union of Conservation of Nature) since 2011. Some factors that might drive this species into extinction ranges from wild attacks in the forest, habitat degradation due to land acquisition for plantation and development areas, and human slaughter because they regard these animals as enemies that sometimes enter community settlements. Elephants in Sembilang National Park is an interesting issue because it has not been registered as key species in Sembilang National Park, as well as no authentic evidence and official reports about the existence of elephants in the park. This paper proves the existence of elephants in Sembilang National Park, South Sumatra. The elephant documentation is in the form of photos and videos of 4 different elephant individuals, footage, cruising lanes and elephant puddles. Evidence of the existence of elephants in Sembilang National Park strongly indicates that future actions, participation and attention of all stakeholders are needed to the conservation efforts of the biggest Sumatran mammals in Sembilang National Park